Assessment of Language Learning Based on Merdeka Curriculum at an Indonesian Junior High School - Zahidannisa, Z; Hikmat, Mauly Halwat (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to find out the application of assessment used by teachers in language learning based on Merdeka Curriculum in Junior High Schools in Indonesia. Methodology: This study used a descriptive qualitative approach, using observation and interviews with 3 English teachers from the same school to collect data. Results: The results of this study show that the implementation of assessment based on the aspects determined by the Independent Curriculum is carried out efficiently by the teachers while still maintaining the basic concept of learning based on the Independent Curriculum. This is evidenced by the synchronization of interview results with classroom observations. Applications/Originality/Value: The results of this study also contribute to a broader understanding of assessment implementation by providing insights into assessment methods in measuring student competence and offering recommendations for aligning assessment practices with the competency-based learning objectives promoted by Merdeka Curriculum.